Analisa Kolusi lndustri Manufaktur Indonesia Tahun 1993-2000 - Nurdianto, Ditya Agung (UI Scholars Hub, 2004)
Despite its shortcomings, many industrial economists believe that concentration index is a powerful tool to use in order to analyze the level of competition within a market. This is due to the fact that concentration index influences greatly market performance. Nonetheless, there are two opposing views on how does concentration index actually influences the market (Donsimoni, 1984). On one hand, the relationship between competition and market performance, and perfect competition with market performance on the other hand, have been discussed since the 18th century, however, a common ground between those two opposing theories have relatively been left untouched by analysis (Bothwell, 1984). Even so, in the last three decades, many researches have been done based on those two opposing theories. Through the use of panel regression in this research, the degree of collusion in the Indonesian manufacturing industry can be found. Although the degree of collusion is small, nevertheless, there exists a positive relationship between the degree of collusion and the level of concentration. This proves that the first theory, Market Power Theory, applies in this case. By knowing that this is the theory which applies in the manufacturing industry in Indonesia, the policy implemented must be adjusted accordingly. Policy implemented by the government for the manufacturing industry should take into account the possibility that collusion exists within certain industries which contain a small amount of large firms that control the majority of the market share.